Relationship Between Neuroticism Personality And Academic Performance - Ahmad Munjirin; Fajra Pahlevi; Diah Karmiyati; Nurul Fajri Assakinah (Amandemen: Journal of Learning, Teaching and Educational Studies, 2023)
Academic success is very important in an individual's life, one form of academic success is academic achievement. Academic achievement is important because of the evaluation results of the educational activity process. One of the factors that influence academic achievement is neuroticism personality. Neuroticism personality is a condition of despair, panic in stressful situations, and negative emotions. The effect of neuroticism on academic performance: 1). Anxiety Tendencies 2). Negative Feelings, 3). Response to criticism, 4). Emotion Regulation. The purpose of the study was to determine the relationship between neuroticism personality and academic achievement. This research uses a literature review study, with the results of systematic literature review conducted from 13 research journals showing that neuroticism personality has a relationship with academic achievement